Cytotoxic and Antifungal Activities of Diverse α-Naphthylamine Derivatives - Kouznetsov, Vladímir V. (2012)
Diverse α-naphthylamine derivatives were easily prepared from corresponding aldimines derived from commercially available a-naphthaldehyde and anilines or isomeric pyridinecarboxyaldehydes and á-naphthylamine. The secondary amines obtained were tested as possible antifungal and cytotoxic agents. The diverse N-aryl-N-[1-(1-naphthyl)but-3-enyl]amines obtained were active (IC50 < 10 µg/mL) against breast (MCF-7), non-small cell lung (H-460), and central nervous system (SF-268) human cancer cell lines, while N-(pyridinylmethyl)-naphthalen-1-amines resulted in activity against (MIC 25-32 µg/mL) some human opportunistic pathogenic fungi including yeasts, hialohyphomycetes, and dermatophytes.